Quantitative Proteomics Reveals Antibiotics Resistance Function of Outer Membrane Proteins in Aeromonas hydrophila - Yao, Zujie; Sun, Lina; Wang, Yuqian; Lin, Ling; Guo, Zhuang; Li, Dong; Lin, Wenxiong; Lin, Xiangmin (Frontiers in Cellular and Infection Microbiology, 2018)
Outer membrane proteins (OMPs) play essential roles in antibiotic resistance, particularly in Gram-negative bacteria; however, they still have many unidentified functions regarding their behavior in response to antibiotic stress. In the current work, quantitative tandem mass tag labeling-based mass spectrometry was used to compare the outer membrane related proteins between an oxytetracycline-resistant (OXY-R) and its original control stain (OXY-O) in Aeromonas hydrophila. Consequently, a total of 261 commonly altered proteins in two biological repeats were identified including 29 proteins that increased and 28 that decreased. Gene ontology analysis showed that the expression of transport proteins was significantly reduced, and translation-related proteins were downregulated in the OXY-R strain. After using western blotting to validate selected altered proteins, eight OMP-related genes were knocked out and their roles in antibiotic resistance were further evaluated. The survival assays showed that some mutants such as ∆AHA-4281, ∆AHA-2766, ∆AHA-2282, ∆AHA-1181, and ∆AHA-1280 affected the susceptibility of A. hydrophila to antimicrobials. Moreover, the minimum inhibitory concentration assay showed that these candidate mutants also respond differently to other types of antibiotics. Our results reveal several novel outer membrane related proteins of A. hydrophila that play important roles in antibiotic resistance, and as such, may be helpful for screening studies to identify novel drug targets.